The burden of congenital Chagas disease and implementation of molecular diagnostic tools in Latin America. Issue 5 (11th October 2018) - Picado, Albert; Cruz, Israel; Redard-Jacot, Maël; Schijman, Alejandro G; Torrico, Faustino; Sosa-Estani, Sergio; Katz, Zachary; Ndung'u, Joseph Mathu
Abstract : It is estimated that between 8000 and 15 000 Trypanosoma cruzi infected babies are born every year to infected mothers in Chagas disease endemic countries. Currently, poor access to and performance of the current diagnostic algorithm, based on microscopy at birth and serology at 8–12 months after delivery, is one of the barriers to congenital Chagas disease (CCD) control. Detection of parasite DNA using molecular diagnostic tools could be an alternative or complement to current diagnostic methods, but its implementation in endemic regions remains limited. Prompt diagnosis and treatment of CCD cases would have a positive clinical and epidemiological impact. In this paper, we analysed the burden of CCD in Latin America, and the potential use of molecular tests to improve access to early diagnosis and treatment of T. cruzi infected newborns.